Editorial - Nain, Manjeet Singh (Indian Journal of Extension Education, 2021)
Extension is positioned to develop and implement high-quality, high-impact experiences for variety of stakeholders. The nature of Extension, work across counties differs because efforts are grounded in the needs of a community. Structural changes in agriculture, new types of agricultural technologies, meagre public budgets, newer policies and government bills, and emerging multifarious type of information and communication technologies usages have led to pluralistic and, in some cases never before mechanisms for implementing extension activities. Sustainability, organic production, oilseed , pulses, climate resilient technologies, nutrition, gender, good agricultural practices, natural resource conservation, information assisted decision making, leadership are the key issues in current scenario in addition to staying healthy in pandemic situation. Historical evidence shows that the epidemics may display potential disarranging effect on civil society in the form of the policy measures tend to conflict with the interest of people, generating friction between society and institutions, differential impacts on society in terms of economic welfare and induction of irrational narratives due to psychological shock. The present issue of the Indian Journal of Extension Education has tried to focus on almost all the recent concerns. I extend my sincere thanks to all the authors for making valuable contributions. The new executive council (2020-23) of Indian Society of Extension Education, New Delhi is in place and started functioning since December 15, 2020 after free and fair ISEE Elections 2020 conducted by a dedicated team. On behalf of Editorial team I extend my sincere thanks to the Election Committee for their dedicated and selfless efforts and to ISEE members who gave chance to serve the professional cause. I extend special thanks to the Editorial Team (2012-20) led by Professor R N Padaria, who handed over Indian Journal of Extension Education in the most updated form. Special thanks are extended to Drs. Himanshu K De, Dr Lalita Vatta and other members of the editorial board for their praiseworthy as well as painstaking efforts in editing the papers. Thanks are due to Drs. Souvik Ghosh, Bhanu Mishra, DK Pandey, Lalit Tyagi, Shafi Afroz, PK Tiwari, JS Gill for sparing their valuable time for reviewing the papers. Special thanks are extended to the President, ISEE; Dr US Gautam for providing insightful thoughts and guidance in bringing out this issue and broadening online sphere of the journal.